A Radiographic Comparison between Successful and Failed Total Contact Casted Patients with Charcot Neuroarthropathy - Avani Chopra BS; Zachary A. Koroneos BS; Christian Benedict BS; Michaela D. Pitcher BS; Michaela D. Pitcher BS; Michael Aynardi MD (Foot & Ankle Orthopaedics)
Category: Midfoot/Forefoot; Hindfoot Introduction/Purpose: This study aims to evaluate the influence of foot deformity severity, as assessed by radiographic measurements, on the efficacy of total contact casting (TCC) in patients with Charcot neuroarthropathy. TCC is a common treatment in this patient population that aims to immobilize the foot and ankle to mitigate trauma, preventing additional damage, and safeguard the foot structure. There is limited data on the optimal radiographic measurement in predicting which patients will be successfully treated with TCC (Griffiths et al., 2021). By comparing radiographic outcomes between patients who were successfully treated with TCC and those who required surgical intervention following TCC failure, we seek to clarify the role of anatomical deformity in treatment prognosis. Methods: We retrospectively analyzed a cohort of Charcot neuroarthropathy patients treated within a single healthcare system. Patients with radiographs of the affected foot within 2 years prior to or 1 year after the initiation of TCC. Patients were divided into two groups: those successfully managed with TCC (n=10) and those necessitating surgery due to TCC failure (n=16). Ten measurements of standard radiographic parameters used for quantifying the level of deformity in Charcot (Wukich et al., 2014) were included in this study. These measurements were Meary’s angle, Calcaneal pitch, medial and lateral column height, calcaneal 5th metatarsal angle, talar declination, tibiotalar angle, Kite’s angle, hindfoot-forefoot angle, and talonavicular coverage angle. All measurements were collected using Phillips PACS Software (Release 4.7) by three trained evaluators with two evaluators assigned per scan. Differences in the average [value] between groups were assessed using an unpaired t-test. Results: The cohort was comprised of 26 patients (16 males, 10 females). Our analysis revealed that lateral column height was the only parameter with a statistically significant difference in the height measurement (p< 0.05) between the groups. There were no other significant differences detected amongst any of the 9 other measurements. Conclusion: This study revealed that there is a lack of significant differences in most radiographic measurements between patients successfully treated with TCC and those requiring surgical intervention. This may suggest that standard radiographic measurements used for characterizing foot deformity does not help to predict the outcomes of TCC for CN. These findings emphasize the need for a more comprehensive understanding of treatment success predictors beyond anatomical considerations.